Muzyka etniczna jako element innowacyjności i modernizacji czeskiego wychowania muzycznego = Ethnic music as a component of innovation and modernisation of Czech music education - Kusák, Jiří (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
This contribution reflects the ethnic music as content, formative and axiological component of innovation and modernisation of the contemporary Czech music. Ethnic music can be considered as a means of intercultural sensitivity and intercultural competence development.
Keywords: muzyka etniczna; wychowanie wielokulturowe; wrażliwość międzykulturowa; kompetencje międzykulturowe; innowacyjność; modernizacja; wychowanie muzyczne; kierunkowo-dydaktyczne przygotowanie nauczyciela; uczeń; ethnic music; multicultural education; intercultural sensitivity; intercultural competence; innovation; modernisation; music education; professional didactic preparation of a teacher; pupil